Translation of Kompositum of German Legal Texts Into Indonesian: A Comparative Analysis Between Google Translate And DeepL - Uryadi, Uryadi; Agustin, Rina; Rachma, Azka Adilya (Interference: Journal of Language, Literature, and Linguistics, 2025)
Abstract. This study examines the translation of kompositum (compound words) in German legal texts into Indonesian through a qualitative comparative analysis of two machine translation tools: Google Translate and DeepL. The analysis is conducted based on three key criteria: accuracy, acceptability, and readability. Selected legal texts containing complex kompositum, such as "ärztliche Bescheinigung für Jugendliche” and “Berufsausbildungsvertrag”, are analyzed to evaluate the performance of each tool in conveying meaning, contextual appropriateness, and linguistic fluency. The findings reveal that both tools demonstrate a high level of accuracy in translating legal kompositum, but DeepL consistently outperforms Google Translate in terms of acceptability and readability, producing more natural and contextually appropriate translations. Google Translate, while accurate, occasionally results in translations that are less fluent and less acceptable in formal contexts. These findings highlight the strengths and limitations of each tool, providing valuable insights for translators and researchers working with German- Indonesian legal texts. Keywords: Kompositum, German legal texts, machine translation, Google Translate, DeepL, accuracy, acceptability, readability, comparative analysis, German-Indonesian translation